2002
DOI: 10.1080/13504850110049405
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Fisher hypothesis for the cases of Argentina, Brazil and Mexico

Abstract: This paper investigates the validity of the Fisher effect hypothesis that it is the interest rate that moves to adjust to anticipated changes in the rate of inflation. The analysis is carried out with monthly data for the period 1980–1997 for three countries that have a recent history of chronic high inflation: Argentina, Brazil and Mexico. A cointegration analysis provided evidence of a stable long-run equilibrium relationship between nominal interest rates and the inflation rate for the cases of Argentina an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Inflation expectations are estimated utilising a five‐month moving average (with two leads and two lags) of actual inflation (C5) as suggested by Yuhn (1996). 5 Pain and Thomas (1997) and Carneiro et al. (2002) also utilise a simple moving average modeling procedure to generate the required expected inflation time series.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflation expectations are estimated utilising a five‐month moving average (with two leads and two lags) of actual inflation (C5) as suggested by Yuhn (1996). 5 Pain and Thomas (1997) and Carneiro et al. (2002) also utilise a simple moving average modeling procedure to generate the required expected inflation time series.…”
Section: Methodsmentioning
confidence: 99%
“…Inflation expectations are estimated utilising a five-month moving average (with two leads and two lags) of actual inflation (C5) as suggested by Yuhn (1996). 5 Pain and Thomas (1997) and Carneiro et al (2002) also utilise a simple moving average modeling procedure to generate the required expected inflation time series. Yuhn (1996) motivates this methodology by pointing out that economic agents make their inflation forecast based on a finite information set that does not span too far into the future.…”
Section: (A) Datamentioning
confidence: 99%
“…The authors contended that for each of these five countries, the real interest rate is non-stationary in levels. Similarly, Carneiro et al (2002) revealed no homogenous results for three big Latin American countries: Mexico, Argentina, and Brazil. The authors' analysis revealed that there appears to be a stable long-run relationship between nominal interest rates and inflation rates just for Argentina and Brazil.…”
Section: Empirical Literature On the Interest Rates−inflation Nexusmentioning
confidence: 89%
“…When the literature is examined, it is seen that there are studies justifying that interest rates are a function of inflation (Equation 5); Barthold and Dougan (1986), Hutchison and Keeley (1989), McDonald and Murphy (1989), Gupta (1991), Woodward (1992), Phylaktis and Blake (1993), Kesriyeli (1994), Pelaez (1995), Peng (1995), Daniels et al (1996), Olekalns (1996), Engsted (1996), Berument et al (1999), Malliaropulos (2000), Lanne (2001), Berument and Jelassi (2002), Atkins and Coe (2002), Carneiro et al (2002), Lardic and Mignon (2003), Million (2004), Turgutlu (2004), Granville and Mallick (2004), Bajo-Rubio et al (2005), Şimşek and Kadılar (2006), Westerlund (2006), Gül and Açıkalın (2008), Westerlund (2008), Tsong and Lee (2009), Bassil (2010), Toyoshima and Hamori (2011), Jareno and Tolentino (2013), Kıran (2013), Doğan, Eroğlu and Değer (2016), İşcan and Kaygısız (2019) detected the existence of a causality relationship from INF to RT in their empirical studies.…”
Section: Rt : Interest Rate Inf : Inflationmentioning
confidence: 99%